2019
DOI: 10.31616/asj.2018.0258
|View full text |Cite
|
Sign up to set email alerts
|

Multifidus Muscles Lipid Content Is Associated with Intervertebral Disc Degeneration: A Quantitative Magnetic Resonance Imaging Study

Abstract: Study Design Cross-sectional study. Purpose To determine the association between fatty degeneration of the multifidus muscle (Mm) and intervertebral disc degeneration (IVDD) using quantitative magnetic resonance imaging (MRI). Overview of Literature Few studies have reported on quantitative MRI analysis of the relation between the Mm and IVDD. Methods The subjects with chronic low back pain comprised 45 patients (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Studies have demonstrated that IMCL are significantly higher in those with chronic LBP and that there is a positive correlation between IMCL and VAS 78–80 . IMCL are also significantly correlated with sagittal alignment and anterior annulus fibrosus degeneration 76,77 . In contrast, EMCL have not been found to be significantly different between chronic LBP and normal groups 76 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that IMCL are significantly higher in those with chronic LBP and that there is a positive correlation between IMCL and VAS 78–80 . IMCL are also significantly correlated with sagittal alignment and anterior annulus fibrosus degeneration 76,77 . In contrast, EMCL have not been found to be significantly different between chronic LBP and normal groups 76 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of the relatively limited accuracy of conventional MRI, several novel MRI modalities have emerged. We found some studies that applied MRS 7,[75][76][77][78][79][80][81] , chemical-shift MRI 51,69,[82][83][84][85] and multi-echo MRI 75 . A comparison of different MRI modalities is included in Table 1.…”
Section: Novel Mri Modalitiesmentioning
confidence: 99%
“…This study followed a previously described MRI protocol [20][21][22][23][24]. Briefly, T2-weighted sagittal and transverse magnetic resonance (MR) images were obtained using the Signa HDx 1.5 T MRI system (GE Healthcare, Milwaukee, WI, USA) with a spine coil.…”
Section: Magnetic Resonance Imaging Protocolmentioning
confidence: 99%
“…MRS data were analyzed according to a previously described method [20][21][22][23][24]. Spectral data were used to measure EMCL and IMCL contents using the LCModel software (Stephen Provencher Inc., Oakville, ON, Canada).…”
Section: Analysis Of Magnetic Resonance Spectroscopy Datamentioning
confidence: 99%
“…Our results indicated that the IMCL of the Mm might be accompanied with posterior AF degeneration. The Mm as well as anterior AF of IVD were important for the function of the lumbar spinal column, and had cross‐correlation each other …”
Section: Ivd and Advances In Diagnostic Imagingmentioning
confidence: 99%